Non-state actors in global governance: Three faces of power - Bas Arts (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2003)
The political power of non-state actors (NSAs) remains a contested issue, as the continuing debates between neo-realists and transnationalists within the Study of International Relations (SIR) show. This paper builds on as well as tries to transcend this debate. Its objective is to bring more 'unity' in the diverse and fragmented NSA literature: (1) by deducing general, case-transcending trends on the political role and impact of NSAs; and (2) by analysing these trends from one specific theoretical framework. The first aspect is achieved by analysing cases from different issue-areas in global governance (environment and human rights), and from the perspective of different types of NSAs (Non-Governmental Organisations, NGOs, and Transnational Corporations, TNCs). The second aspect is achieved by applying 'the three faces of power framework'. Inspired by and derived from the academic debates on the concept of power, these faces consists of: (1) decisional power, related to policy making and political influence; (2) discursive power, related to the (re)framing of discourses; and(3) regulatory power, related to rule-making and standard-setting.In the paper, these three faces are applied to three cases: to the IUCN and the UN Framework Convention on Biological Diversity, to NGOs and the human rights regime as well as to industry and environmental standards (Responsible Care Initiative and ISO 14001 respectively). These cases substantiate the view that NSAs are capable of reshaping patterns and outcomes of global governance, through the three faces of power.
Keywords: 330; Nichtregierungsorganisation; Internationale Wirtschaftspolitik; Multinationales Unternehmen; Welt